2022
DOI: 10.1111/ajsp.12555
|View full text |Cite
|
Sign up to set email alerts
|

Testing the status‐legitimacy hypothesis: Predicting system justification using objective and subjective socioeconomic status in China and the United States

Abstract: The status-legitimacy hypothesis proposes that those who are most disadvantaged by unequal social systems are even more likely than members of more advantaged groups to provide ideological support for the very social system that is responsible for their disadvantages. Li, Yang, Wu, and Kou (2020, Personality and Social Psychology Bulletin) sought to expand the generalizability of this hypothesis by testing it in China, addressing inconsistencies surrounding the empirical support for this hypothesis by postulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Another way to reconcile this discrepancy is by focusing on the subjective vs. objective nature of the two SES measures. Previous studies demonstrated that objective, albeit not subjective, measures of SES negatively predicted system justifying beliefs (Buchel et al, 2021;Li et al, 2020;Valdes et al, 2023). One plausible interpretation of these results is that the status legitimacy hypothesis pertains to contextual effects of social class and that SES effects are probably mediated by the sense of powerlessness which is more common in objectively disadvantaged individuals (Buchel et al, 2021;Van Der Toorn et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Another way to reconcile this discrepancy is by focusing on the subjective vs. objective nature of the two SES measures. Previous studies demonstrated that objective, albeit not subjective, measures of SES negatively predicted system justifying beliefs (Buchel et al, 2021;Li et al, 2020;Valdes et al, 2023). One plausible interpretation of these results is that the status legitimacy hypothesis pertains to contextual effects of social class and that SES effects are probably mediated by the sense of powerlessness which is more common in objectively disadvantaged individuals (Buchel et al, 2021;Van Der Toorn et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, we build upon different strands of literature to identify the role of each of the three aforementioned psychological mechanisms (Figure 1) best explain the relationship between SES and left-right voting intentions. Given that different dimensions of SES are often associated with distinct psychological mechanisms (Buchel et al, 2021;Valdes et al, 2023;Willis et al, 2022;Yang et al, 2019), we differentiate between education and subjective income and we compare the effects of these two measures of SES on left-right voting intentions. To accomplish these goals, we use novel data that consists of large representative samples from nine European countries.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from China, which is a non-democratic society with relatively high scores on the dimension of “power distance” (Hofstede 1991), Li et al (2020) demonstrated that individuals with lower subjective socio-economic status are more likely to support existing social structures consistent with system justification theory. Recently, Valdes, Liu, and Williams (2022), replicated the findings that individuals with lower subjective socio-economic status have enhanced system justification tendencies in both the United States and China.…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…In this study, we included measures of subjective SES, objective SES and political orientation. There is evidence that all three of these constructs correlate with system justification (Feygina et al., 2010; Li et al., 2020; Valdes et al., 2022).…”
Section: Studymentioning
confidence: 99%